MATH SOLVE

4 months ago

Q:
# Consider the sequence of steps to solve the equation: 3(x − 4) + 5x = 9x − 36 Given ⇒ 3(x − 4) + 5x = 9x − 36 Step 1 ⇒ 3x − 12 + 5x = 9x − 36 Step 2 ⇒ 3x + 5x − 12 = 9x − 36 Step 3 ⇒ 8x − 12 = 9x − 36 Step 4 ⇒ 8x − 8x − 12 = 9x − 8x − 36 Step 5 ⇒ 0 − 12 = x − 36 Step 6 ⇒ −12 = x − 36 Step 7 ⇒ −12 + 36 = x − 36 + 36 Step 8 ⇒ 24 = x + 0 Step 9 ⇒ 24 = x Which property yields Step 1?

Accepted Solution

A:

Answer:B) Additive Identity Property. Step-by-step explanation:Let us consider the definition of Additive Identity Property: The additive identity property states that if you add a real number to zero or add zero to a real number, then you get the same real number back. The number zero is known as the identity element, or the additive identity. In Step 5 we can see that, [tex]0-12 = x - 36[/tex]In Step 6 we get, [tex]-12= x-36[/tex]So basically, [tex]0-12 = -12[/tex]We know that [tex]-12[/tex] is a real number and if a real number is added to 0, we get the real number back, so in step 6 we got -12. Therefore, additive identity property yields step 6.